Aspek Hukum Subyek Pajak Bentuk Usaha Tetap Menurut Hukum Positif di Indonesia - Paulus Aluk Fajar Dwi Santo (Binus Business Review, 2010)
PE (Permanent Establishment) is an international tax terminology which is a consequence of the operations of the base/fixed sites in the treaty partner country, after fulfilling certain conditions stipulated in the Tax Treaty or the Act, such as: types of business activities conducted in the country treaty partner, source of income and the term ("Time Test"). The existence of permanent establishments of this affect a country's right to impose a tax on the object is meant. Status BUT in practice still needs to be studied again, the research method used is a historical-juridical, comparatif and analytical as well as using interview techniques. Travel Tax Act in determining the status BUT we found frequent changes eg, in the 1925 Corporate Tax BUT as the subject of placing a foreign tax, then Law No. 7 / 1983 BUT put as the subject of domestic taxes and the Law No. 10 years in 1994 stutus BUT reinstated as foreign tax subject until now. There are also difficulties associated with determining the condition of BUT for certain conditions eg how to define a PE for a transaction that uses E-Commerce. It would need to be reviewed relates to the status of PE as a tax subject and also have already started to set up regulations relating to the determination of a PE are complete.